Social identity and crisis resilience in agriculture: Caste, gender, and migration in Nepal - Alvi, Muzna; Barooah, Prapti; Saini, Smriti; Kishore, Avinash (Wiley, 2025)
Capacity to weather economic shocks is often mediated by social identity, which in turn determines access to social, economic and physical capital. We study the repercussions of a large economic shock on access to agriculture inputs, agricultural extension, output markets, and the consequent effects on income and livelihoods in rural Nepal. We focus on heterogeneity by caste, gender, and household migration status, using panel survey data from 2300 maize farmers. We observe prolonged effects of the 2020 pandemic induced lockdowns on the incomes of farmers, driven in part by reduced remittances. The shock intensified inequalities in agriculture, especially for female farmers and farmers from disadvantaged caste groups. As the economic impacts of multiple crises continue, policy measures to support the agriculture sector should target disadvantaged farmers, while simultaneously implementing long term strategies to shield the agriculture sector from future shocks.